Making Government Accountable: Lessons from a Federal Job Training Program. - Courty, Pascal; Marschke, Gerald (Public Administration Review, 2007)
This article describes the evolution of a performance measurement system in a government job training program. In this program, a federal agency establishes performance measures and standards for substate agencies. The performance measurement system’s evolution is at least partly explained as a process of trial and error characterized by a feedback loop: The federal agency establishes performance measures, the local managers learn how to game them, the federal agency learns about gaming and reformulates the performance measures, possibly leading to new gaming, and so on. The dynamics suggest that implementing a performance measurement system in government is not a one-time challenge but benefits from careful monitoring and perhaps frequent revision.